The legal framework of the Constitution and printing. (Herald of Journalism, 2016)
The article focuses on the legal opinions biys a democracy steppe, the first draft of the Constitution is analyzed, as well as media coverage of the important parts of the Constitution. The author tries to cover the legal bases in journalism.
Keywords: law; Constitution; ethics; hadith; democracy; journalism; reader.